Mutagenesis of human DNA polymerase lambda: essential roles of Tyr505 and Phe506 for both DNA polymerase and terminal transferase activities. - Shevelev, I; Blanca, G; Villani, G; Ramadan, K; Spadari, S; Hübscher, U; Maga, G (2003)
DNA polymerase (pol) lambda is homologous to pol beta and has intrinsic polymerase and terminal transferase activities. However, nothing is known about the amino acid residues involved in these activities. In order to precisely define the nucleotide-binding site of human pol lambda, we have mutagenised two amino acids, Tyr505 and the neighbouring Phe506, which were predicted by structural homology modelling to correspond to the Tyr271 and Phe272 residues of pol beta, which are involved in nucleotide binding. Our analysis demonstrated that pol lambda Phe506Arg/Gly mutants possess very low polymerase and terminal transferase activities as well as greatly reduced abilities for processive DNA synthesis and for carrying on translesion synthesis past an abasic site. The Tyr505Ala mutant, on the other hand, showed an altered nucleotide binding selectivity to perform the terminal transferase activity. Our results suggest the existence of a common nucleotide-binding site for the polymerase and terminal transferase activities of pol lambda, as well as distinct roles of the amino acids Tyr505 and Phe506 in these two catalytic functions.